Comparison of the Effectiveness of Paracetamol and Ibuprofen in the Management of Patent Ductus Arteriosus in Preterm Neonates: A Randomized Controlled Trial - S. Mohsin Ali Shah; Shaista Azeem Khan; Faran Sadiq; Ruba Gul; Faizan Sadiq; Misbah Ullah Khan; Muhammad Khalid Khan; Faryal Uzma; Arooj Khan; Sabir Khan (Molecular and Cellular Pediatrics)
Abstract Background Patent ductus arteriosus is one of the most common cardiac conditions affecting the neonates. Considering the lack of studies done on this topic in healthcare settings in Khyber Pakhtunkhwa province, this study aims to find out the comparative effectiveness of paracetamol and ibuprofen in management of PDA in our healthcare setting to conclude a better management option for the condition. Objective To find and compare the effectiveness of paracetamol and ibuprofen in the closure of patent ductus arteriosus in preterm neonates. Methodology This randomized controlled trial was conducted in the Department of Nursery and Neonatal Intensive Care Unit, Khyber Teaching Hospital, Peshawar, Pakistan, from 10th April 2024 to 10th October 2024. A total of 256 neonates of both genders with patent ductus arteriosus were included. Group A received oral paracetamol, and Group B received oral ibuprofen. The effectiveness of the treatments was evaluated at the end of the treatment period. Results The age range in this study was from 48 to 96 h, with a mean age of 71.79 ± 13.10 h in Group A and 73.40 ± 11.81 h in Group B. Efficacy was observed in 107 (83.6%) patients in Group A compared to 90 (70.3%) patients in Group B, showing a statistically significant difference (P = 0.011). Conclusion Our study has concluded that paracetamol is more effective than ibuprofen in closing patent ductus arteriosus. The trials were retrospectively registered at NIH Trial Registry (NCT06601114) https://clinicaltrials.gov/study/NCT06601114 dated 15/09/2024.